2009
DOI: 10.1074/jbc.m808054200
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of the Oxidoreductase ERp57 Is Determined Primarily by Its Interaction with Calnexin and Calreticulin

Abstract: The formation of disulfides within proteins entering the secretory pathway is catalyzed by the protein disulfide isomerase family of endoplasmic reticulum localized oxidoreductases. One such enzyme, ERp57, is thought to catalyze the isomerization of non-native disulfide bonds formed in glycoproteins with unstructured disulfide-rich domains. Here we investigated the mechanism underlying ERp57 specificity toward glycoprotein substrates and the interdependence of ERp57 and the calnexin cycle for their correct fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 29 publications
4
60
0
Order By: Relevance
“…Indeed, a recent study confirmed that the 27-kDa form of Prx IV is produced as the result of cleavage of the NH 2 -terminal 36 residues of the encoded protein (11). This study also showed, however, that the 27-kDa form of Prx IV is retained within the ER despite the fact that it lacks a recognized ER retention motif (11,12). Both the 27-and 31-kDa forms of Prx IV thus appear to be localized to the ER, whereas other 2-Cys Prx isoforms are located in the cytoplasm (Prxs I and II) or mitochondria (Prx III) (4).…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Indeed, a recent study confirmed that the 27-kDa form of Prx IV is produced as the result of cleavage of the NH 2 -terminal 36 residues of the encoded protein (11). This study also showed, however, that the 27-kDa form of Prx IV is retained within the ER despite the fact that it lacks a recognized ER retention motif (11,12). Both the 27-and 31-kDa forms of Prx IV thus appear to be localized to the ER, whereas other 2-Cys Prx isoforms are located in the cytoplasm (Prxs I and II) or mitochondria (Prx III) (4).…”
supporting
confidence: 56%
“…Prx IV in the ER physically interacts with PDI. Prx IV-S is thus thought to function as a sensor of H 2 O 2 in PDI-mediated protein folding (12,26). Similar to the proposed function of Prx IV-S in the ER, Prx IV-L may sense H 2 O 2 in the cytosol and mediate the formation of disulfide linkages in proteins that participate in chromatin condensation and contribute to the supramolecular structure of the sperm tail.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This ER-soluble protein interacts with the two lectin chaperones, calreticulin and calnexin, to promote folding of newly synthesised proteins by catalysing the formation of disulphide bonds (Russell et al 2004). ERP57 interacts with glycoproteins during their folding and corrects disulphide bond formation and hence it catalyses the re-folding of mis-folded proteins (Jessop et al 2002). In this study, ERP57 expression increased in the caruncular tissue at the time of implantation and during early pregnancy.…”
Section: Protein Synthesis and Degradationmentioning
confidence: 61%
“…ERp57 lacks inherent substrate binding capabilities and interacts with its substrates through the lectins calnexin and calreticulin, which act as adaptors to supply the redox-active site with suitable substrates. The interaction with these lectins primarily determines the substrate specificity of ERp57 (40), which preferentially acts on a glycosylated subset of folding substrates.…”
Section: Discussionmentioning
confidence: 99%